Proactive role-orientation toward workplace safety: Psychological dimensions, nomological network and external validity. (August 2016) - Curcuruto, Matteo; Mearns, Kathryn J.; Mariani, Marco G.
Highlights: A new model is developed to describe the psychological drivers of safety proactivity. A multidimensional measurement tool (PRO-SAFE) is tested in two industrial contexts. Factor analyses evidence the goodness of the hypothesized factor structure. The PRO-SAFE general measure correlates with measures of safety initiative and voice. In sum, empiric evidences support construct and nomological validities of PRO-SAFE. Abstract: In the light of the relevance of workers' participation and initiative in improving safety in the workplace, a new measurement tool is presented to assess multiple psychological drivers (proactive motivations; future orientations) which support a proactive orientation by individuals toward safety management and accident prevention in the workplace. This validation study was developed with a survey methodology in two industrial samples ( N = 327; 196) from the chemical and manufacturing sectors. The factor structure of the tool was tested with CFA's. The analyses evidenced the goodness of a multidimensional structure, with a general superordinate dimension indicator of the overall construct of individuals' proactive safety-role orientation. Moreover, the analysis of the nomological network of the new model showed positive correlations with both behavioral criteria (safety voice; safety initiative) and supervision antecedents (safety-specific transformational leadership) which were measured at the individual level. Finally, the external validity was positively verified by significant correlations with organizational outcomes assessed at the team level through external measures (supervisor evaluations; data archives) which were collected at team level ( N = 32) in the following six months from the main survey. Theoretical and practical implications with indications for future research conclude the article.